2011
DOI: 10.2165/11586170-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Pathophysiology and Medical Management of Postoperative Ileus in the Elderly

Abstract: As the population of the Western world ages, the number of major surgical procedures performed in the elderly population will by necessity increase. Within virtually every surgical specialty, studies have shown that patients should not be denied surgery on the basis of chronological age alone. It has recently been recognized that physiological age is far more important within the decision-making algorithm as to whether or not to proceed with major surgery in the septuagenarian and octogenarian populations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…This study found that age of 65 years old or older and duration of surgery are the risk factor associated with post-operative ileus with RR of 5.96 and 6.14, respectively. Hirayasa et al found that the risk of post-operative ileus is higher in elderly patients who undergone colorectal surgery (65 years old or older) compare to younger population (1.8 -19.6 vs. 0.8 -7.9) [7]. Some other studies are in line with the finding of this study.…”
Section: Discussionsupporting
confidence: 91%
“…This study found that age of 65 years old or older and duration of surgery are the risk factor associated with post-operative ileus with RR of 5.96 and 6.14, respectively. Hirayasa et al found that the risk of post-operative ileus is higher in elderly patients who undergone colorectal surgery (65 years old or older) compare to younger population (1.8 -19.6 vs. 0.8 -7.9) [7]. Some other studies are in line with the finding of this study.…”
Section: Discussionsupporting
confidence: 91%
“…An advanced age might correlate with a higher prevalence of POI because elderly patients are more vulnerable to surgical stress, which might more easily cause impaired bowel contractility and motility as well as gut wall edema . Strategies including laparoscopic technique, fast‐track recovery protocol and early enteral nutritional support can reduce POI and promote post‐operative recovery …”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients have higher levels of comorbidity, frailty and social care requirements . It may be argued that the elderly need strategies such as ERAS to optimize speed of recovery and to avoid postoperative complications and their sequelae . The aim of this review was to determine the evidence for the safety, feasibility and efficacy of an enhanced recovery programme after colorectal surgery in elderly patients.…”
Section: Introductionmentioning
confidence: 99%